Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional, Kecerdasan Spiritual, dan Faktor Situasional Pada Keputusan Etis Konsultan Pajak - Muliartini, Ni Wayan; Jati, I Ketut (E-Jurnal Akuntansi; Vol 28 No 3 (2019)DO - 10.24843/EJA.2019.v28.i03.p15, 2019)
The purpose of this study was to obtain empirical evidence on how the influence of intellectual intelligence, emotional intelligence, spiritual intelligence, and situational factors on the ethical decisions of tax consultants in Bali. The number of samples are 79 respondents at 69 tax consultant offices in Bali with purposive sampling technique, Tax consultant who handles clients and unlimited positions and has USKP certificate. Data collection is done by questionnaire method. The analysis technique used in the research is multiple regression analysis. The results shows that intellectual intelligence, emotional intelligence, spiritual intelligence has positive effect on the ethical decisions of tax consultants. Professional relations had a negative effect on tax consultant ethical decisions, but risk preferences and information current did not significantly influence the tax consultant's ethical decisions. Keywords : Intellectual Intelligence, Emotional Intelligence, Spiritual Intelligence, Risk Preference.